Family relations in the age of social media: How Jordanians view the influence of Facebook and WhatsApp - Darwish, Noor; Darwish, Taha; Haider, Ahmad S (Research Journal in Advanced Humanities, 2025)
This study investigates the influence of social media platforms, particularly Facebook and WhatsApp, on family life and marital relationships in Jordan, with attention to their potential link to rising divorce rates. The research addresses a growing concern about how digital communication technologies affect trust, cohesion, and everyday family interactions. A quantitative survey was conducted with 100 married participants residing in Amman, Jordan. Data were collected using structured questionnaires designed to capture perceptions of spousal trust, relationship quality, and family dynamics in relation to social media use. The findings reveal that while most respondents acknowledged the negative impact of Facebook and WhatsApp on spousal communication and family cohesion, perceptions of trust were more complex. Specifically, 72% reported no strengthening of marital bonds through social media use, yet 82% did not believe mistrust had increased. Participants attributed this to shared cultural, religious, and ethical values that reinforced marital trust. Nonetheless, over half observed that excessive time on social media disrupted face-to-face communication, family mealtimes, and overall cohesion. In conclusion, social media use among Jordanian families presents a double-edged sword: while enabling global connectivity and access to diverse perspectives, it also risks weakening intimate communication and contributing to marital discord. These findings highlight the need for further research into cultural, generational, and psychological dimensions of social media use, particularly its impact on children and long-term family stability.